Salience attribution and its relationship to cannabis-induced psychotic symptoms. Issue 16 (15th September 2016) - Bloomfield, M. A. P.; Mouchlianitis, E.; Morgan, C. J. A.; Freeman, T. P.; Curran, H. V.; Roiser, J. P.; Howes, O. D.
Abstract : Background: Cannabis is a widely used drug associated with increased risk for psychosis. The dopamine hypothesis of psychosis postulates that altered salience processing leads to psychosis. We therefore tested the hypothesis that cannabis users exhibit aberrant salience and explored the relationship between aberrant salience and dopamine synthesis capacity. Method: We tested 17 cannabis users and 17 age- and sex-matched non-user controls using the Salience Attribution Test, a probabilistic reward-learning task. Within users, cannabis-induced psychotic symptoms were measured with the Psychotomimetic States Inventory. Dopamine synthesis capacity, indexed as the influx rate constant K i cer, was measured in 10 users and six controls with 3, 4-dihydroxy-6-[ 18 F]fluoro-l -phenylalanine positron emission tomography. Results: There was no significant difference in aberrant salience between the groups [ F 1, 32 = 1.12, p = 0.30 (implicit); F 1, 32 = 1.09, p = 0.30 (explicit)]. Within users there was a significant positive relationship between cannabis-induced psychotic symptom severity and explicit aberrant salience scores ( r = 0.61, p = 0.04) and there was a significant association between cannabis dependency/abuse status and high implicit aberrant salience scores ( F 1, 15 = 5.8, p = 0.03). Within controls, implicit aberrant salience was inversely correlated with whole striatal dopamine synthesis capacity ( r = −0.91, p = 0.01), whereas this relationship was non-significant within users (difference between correlations: Z = −2.05, p = 0.04). Conclusions: Aberrant salience is positively associated with cannabis-induced psychotic symptom severity, but is not seen in cannabis users overall. This is consistent with the hypothesis that the link between cannabis use and psychosis involves alterations in salience processing. Longitudinal studies are needed to determine whether these cognitive abnormalities are pre-existing or caused by long-term cannabis use.